Effect of oxygen vacancy segregation in Au or Pt/oxide hetero-interfaces on electronic structures. Issue 57 (19th July 2017) - Shitara, K.; Kuwabara, A.; Fisher, C. A. J.; Ogawa, T.; Asano, T.; Kaneko, Y.; Omote, A.; Moriwake, H.
Abstract : We investigated the effects of oxygen vacancy segregation on electronic structures in the vicinity of hetero-interfaces between noble metals (Au and Pt) and yttria stabilized zirconia by performing first-principles calculations and Bader analysis. Abstract : We investigated the effects of oxygen vacancy segregation on electronic structures in the vicinity of hetero-interfaces between noble metals (Au and Pt) and yttria stabilized zirconia (YSZ) by performing first-principles calculations and Bader analysis. The density of states (DOS) of the Au/YSZ interface around the Fermi level is less than that of the Pt/YSZ interface, resulting from the lower density of Au-s and -p orbitals around the Fermi level compared with the higher density of Pt-d orbitals. Metal layers adjacent to the interface become negatively charged when the bonding oxygen layer contains a high concentration of oxygen vacancies. These results indicate that segregation of oxygen vacancies to Au or Pt/YSZ hetero-interfaces increase the electronic conductivity of Au or Pt atom layers at the interfaces.